Implementation of Pancasila Values and Unity in Diversity as the Basis for Implementation of Learning and Strengthening Pancasila Student Profiles: Implementation of Pancasila Values and Unity in Diversity as the Basis for Implementation of Learning and Strengthening Pancasila Student Profiles - Ana Bella Philia (LPPM Institut Studi Islam Sunan Doe, 2022)
This study aims to identify and describe the implementation of the values of Pancasila and Unity in Diversity as the basis for implementing learning and strengthening the profile of Pancasila students. This study uses a librarian study approach that examines and discusses literature review from various sources, both sources from books, journals and relevant previous studies and the method used is a qualitative method which is used to describe or describe this research. The results showed that at SMA Negeri 1 Palembang, the values of Pancasila and Bhinneka Tunggal Ika in the school ecosystem or environment play a role in overcoming diversity, including religion, race, culture, gender and social status within the school environment, and students who have Pancasila personality as a result of education in schools will become the next generation of a strong nation so that later it will be able to face negative influences from outside and negative influences from globalization. so that the values of Pancasila and Bhinneka Tunggal Ika will produce students who are based on the attitudes of Pancasila student profiles.